If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Xy + 5y = x Reorder the terms: 5y + yX = x Solving 5y + yX = x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Reorder the terms: -1x + 5y + yX = x + -1x Combine like terms: x + -1x = 0 -1x + 5y + yX = 0 The solution to this equation could not be determined.
| -6(x-2)=-6(x+2) | | 10x+10=15x-5 | | 1+k=-11+5k | | 11x+5=5x+15 | | -44=4z | | (7x+6)+(5x+3)=90 | | 7=3+k | | 74-60x=300 | | -2h=-18 | | 6+5x=-4x+57 | | c=35+0.03 | | ln(2x+6)=7 | | 0.7W+164w=27.28 | | ln(2x+6)=6 | | 8x+2=114 | | s/5=-13 | | -3+13=12x-5-11x | | (2x-3)(2x+3)-4x(x+1)=2(x+3)+3 | | 2q-2=23 | | .35=.50 | | 2m-(x+2)=0 | | log4x=5/2 | | (X+2y)(x^3-2x^2y+4xy^2)= | | 3-1/2x=-5 | | 4x=-7y-37 | | 9x-3+2x+20=15+4x+2+7x | | 2x+17-7x-6=8-10x-19+5x | | (5x+3)2y=43 | | 5(3x+3)-5x=95 | | (3x-6)+(5x+9)= | | (7x+2)2= | | (7/9)+(5/6)=x |